Interaction between writing apprehension, motivation, attitude and writing performance: a structural equation modeling approach - Abu Kassim, Noor Lide; Mat Daud, Nuraihan; Mat Daud, Nor Shidrah (IDOSI Publication, 2013)
This study modeled the relationship between various psychological dimensions (motivation,language aptitude and attitude towards language) that have been hypothesised to affect writing apprehension and performance. The method used in this study is the testing of a structural model through the use of structural equation modeling (SEM). Results of the analysis indicated good model-data fit. The Chi-square measure was 97.369, with 97 degrees of freedom, p = 0.470. The nonsignificant p-value, which was above 0.05, indicated an acceptable correspondence of data to the model. The normed chi-square value was found to be within the recommended range (3.0>x2/df>1.0) and the RMSEA (Root Mean Suare Error of Approximation) was below 0.05. The incremental fit indices (normed fit index (NFI) and Tucker-Lewis Index) were above 0.95. The goodness-of-fit index (GFI) which is an absolute fit measure was also above the recommended value. In terms of parsimony, the model showed reasonable estimates (.81). The results also indicated that writing apprehension, motivation and general language proficiency have a significant effect on writing performance and together they accounted for 46% of the variance in writing performance. Attitude towards language, on the other hand, showed a nonsignificant effect.